Effects of Fullerene Bisadduct Regioisomers on Photovoltaic Performance. (19th July 2013) - Meng, Xiangyue; Zhao, Guangyao; Xu, Qi; Tan, Zhan'ao; Zhang, Zhuxia; Jiang, Li; Shu, Chunying; Wang, Chunru; Li, Yongfang
<x xml:space="preserve">Abstract</x> Fullerene bisadducts have emerged as promising electron‐accepting materials because of their ability to increase the open‐circuit voltage (VOC) of polymer solar cells (PSCs) due to their relatively high lowest unoccupied molecular orbital (LUMO) energy levels. It should be noted that the as‐prepared fullerene bisadducts are in fact a mixture of isomers. Here, the effects of fullerene bisadduct regioisomers on photovoltaic performance are examined. The trans‐2, trans‐3, trans‐4, and e isomers of dihydronaphthyl‐based [60]fullerene bisadduct (NCBA) are isolated and used as acceptors for P3HT‐based PSCs. The four NCBA isomers exhibit different absorption spectra, electrochemical properties, and electron mobilities, leading to varying PCE values of 5.8, 6.3, 5.6, and 5.5%, respectively, which are higher than that based on an NCBA mixture (5.3%), suggesting the necessity to use the individual fullerene bisadduct isomer for high‐performance PSCs.